ANALISA GAYA LAGU KLASIK GAMBANG KROMONG “POBIN KONG JI LOK’ - Imam Firmansyah (Universitas Mercu Buana, 2019)
Nowadays, the existing repertoire of the classic songs of gambang kromong is very apprehensive. Dozens of gambang kromong's classical songs developed comprehensively at the end of the 18th century, but in the present, there is only one song that is still possible to play, namely